2011
DOI: 10.5402/2011/856849
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Effect of Carbon Nanotubes and Carbon Fibres on the Behavior of Plain Cement Mortar Composite Round Bars under Direct Tension

Abstract: This paper investigates the behavior of reinforced cement mortar composite round bars with multiwalled carbon nanotubes (MWCNTs) and carbon fibers (CFs). The percentage of CFs was fixed at 2.25 wt% of cement, while the percentage of MWCNTs was fixed at 0.5, by wt% of cement. Dispersion of both MWCNTs and CFs was carried out using ultrasonic energy method. Composite round bars were tested under direct tension in order to evaluate their mechanical properties such as ultimate load, deflection criteria, and stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Manzur and Yazdani [17] in 2010 observed increase in compressive strength of cement mortar through addition of two different sizes of untreated commercial MWNT. Hunashyal et al [18] in 2011 obtained higher tensile strength and better stress-strain relationship in direct tension for cement samples with CNT. Han et al [19] in 2013 showed that addition of MWNT could decrease both water sorptivity and permeability coefficient of CNT reinforced cement-based materials.…”
Section: Introductionmentioning
confidence: 97%
“…Manzur and Yazdani [17] in 2010 observed increase in compressive strength of cement mortar through addition of two different sizes of untreated commercial MWNT. Hunashyal et al [18] in 2011 obtained higher tensile strength and better stress-strain relationship in direct tension for cement samples with CNT. Han et al [19] in 2013 showed that addition of MWNT could decrease both water sorptivity and permeability coefficient of CNT reinforced cement-based materials.…”
Section: Introductionmentioning
confidence: 97%
“…In cement composites, carbon fibers (CFs) can be applied alone or in combination with carbon nanotubes. The behavior of reinforced cement mortar composites round bars with MWCNTs (0.5 wt%; diameter 10-30 nm, length 1-2 μm, surface area 350 m 2 /g) and CFs (2.25 wt%; length of fiber 5 mm, fiber thickness 0.3 mm), ultrasonically dispersed in the cement matrix, was elucidated [27]. Composite round bars were tested under direct tension, in order to evaluate their mechanical properties, such as ultimate load, deflection criteria, and stressstrain behavior.…”
Section: Improvement Of Concrete Properties By Addition Of Cnts and Cnfsmentioning
confidence: 99%
“…The particle size of the filler can be optimally selected so that the filler can increase the hydration reaction, but not significantly affect the dimensional stability of the cement system. The addition of small non-reactive filler to the cement modifies the hydration reaction mainly due to dilution, modification of particle size distribution, and heterogeneous nucleation [8,9].…”
Section: Introductionmentioning
confidence: 99%